Pengaruh Kepuasan Kerja Dan Komitmen Terhadap Produktivitas Kerja Karyawan Pada PT. Wings Karawang - Evha Khoirunnisa; Sungkono (Jurnal Ekonomi dan Bisnis Digital, 2024)
Employee work productivity is one of the key factors in the operational success of a company. Job satisfaction is the level of positive feelings that employees have towards their work. Employee commitment refers to how much employees feel tied to the company and their desire to continue working at the company. This research aims to examine the influence of job satisfaction and commitment on employee work productivity at PT. Wings Karawang. The research method used is a quantitative method with a survey approach. Data collected through questionnaires distributed to 35 employees of PT. Wings Karawang. Data analysis was carried out using multiple linear regression. So the results of this research show that job satisfaction has a positive and significant influence on employee work productivity. Because employees who have high job satisfaction tend to show better productivity. Commitment also has a positive and significant influence on employee work productivity. Employees who are committed to work tend to have optimal work productivity. The conclusion of this research is that increasing job satisfaction and commitment can increase employee work productivity at PT. Wings Karawang.